1991
DOI: 10.1111/j.1476-5381.1991.tb12223.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine‐5′‐O‐(2‐thiodiphosphate) is a potent agonist at P2 purinoceptors mediating insulin secretion from perfused rat pancreas

Abstract: 1 The effects of a P2 purinoceptor agonist, adenosine 5'-O-(2-thiodiphosphate) (ADP-fl-S) have been studied on insulin secretion and flow rate of the isolated perfused pancreas of the rat. 2 In the presence of a moderately stimulating glucose concentration (8.3mM), ADP-f8-S (4.95-495nM) evoked a biphasic insulin response in a concentration-dependent manner. A comparison of relative potency between ADP-fl-S and adenosine 5'-triphosphate (ATP) showed that ADP-f-S was 100 times more potent than ATP. On the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…ADP stimulates insulin secretion from beta cells via the Gα qcoupled P2Y 1 receptor and inhibits insulin release via the Gα i -coupled P2Y 13 receptor [30]. This finding may explain the sometimes contradictory results from previous studies [9][10][11][12][13] where ADP has been shown to both increase [9][10][11] and decrease [12,13] insulin release via P2Y receptors. ADP acting on P2Y 1 receptors has been reported to increase pulsatility of insulin release, but not Ca 2+ rhythmicity in intact pancreas [16].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…ADP stimulates insulin secretion from beta cells via the Gα qcoupled P2Y 1 receptor and inhibits insulin release via the Gα i -coupled P2Y 13 receptor [30]. This finding may explain the sometimes contradictory results from previous studies [9][10][11][12][13] where ADP has been shown to both increase [9][10][11] and decrease [12,13] insulin release via P2Y receptors. ADP acting on P2Y 1 receptors has been reported to increase pulsatility of insulin release, but not Ca 2+ rhythmicity in intact pancreas [16].…”
Section: Discussionmentioning
confidence: 94%
“…A large number of studies indicate that extracellular ATP and ADP have a key role in regulating insulin secretion by purinoreceptors [9][10][11][12][13]. Insulin-secretory granules contain 3.5 mmol/l ATP and 5 mmol/l ADP [14], and with a novel biosensor it has been demonstrated that glucose stimulation releases ATP from a single pancreatic beta cell to a local extracellular ATP concentration exceeding 25 µmol/l [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hyperglycaemia evoked an increase in insulinemia ( + 44 ± 7 ;Lu ml-' at 30 min). When ADPPS (0.1 mg kg-') was added to the glucose solution, increments in plasma insulin levels were significantly higher from 5 min ( + 90 ± 13 ftu ml-' at Table 1 Effects of an intravenous injection of adenosine-5'-O-(2-thiodiphoshate) (ADPPS, 0.1 mg kg-') on arterial blood pressure (mmHg) and venous pancreaticoduodenal blood flow (ml min-') in anaesthetized, fasted dogs (Bertrand et al, 1991). In anaesthetized fasted dogs, the peripheral intravenous injection of ADP,BS induced an immediate but only transient increase in pancreaticoduodenal insulin which was followed by a slight reduction in blood glucose levels; these reached values comparable to basal glycaemia recorded in fasted conscious dogs.…”
Section: Assaysmentioning
confidence: 99%
“…By use of 2-methylthio ATP, these receptors have been shown to belong to the P2y subtype (Bertrand et al, 1987). Recently a specific and more stable P2y-agonist, adenosine-5'-0-(2-thiodiphosphate) (ADPPS), was found to be one hundred times more potent than ATP, and effective in the nanomolar range in stimulating insulin secretion in vitro on perfused rat pancreas (Bertrand et al, 1991).…”
Section: Introductionmentioning
confidence: 99%